YOUTH AND VIOLENCE: CONSIDERATIONS ON THE CONDITIONS OF YOUTH RESOCIALIZATION IN CONTEMPORARY BRAZIL (VERUM: Journal of Scientific Initiation, 2025)
The increase in delinquent acts has become a key topic in discussions related to juvenile justice in the national context. In this regard, the role of the ECA (Statute of the Child and Adolescent – Law No. 8.069/90) and SINASE (National Socio-Educational Assistance System – Law No. 12.594/12) in developing socio-professionalizing activities is debated to advance the socio-educational system and reduce recidivism among this age group. This research aimed to analyze the challenges faced in implementing and expanding public and private initiatives during the fulfillment of socio-educational measures. The methodology used consisted of a narrative literature review on this topic, specifically in Brazil, over the last five years. The data revealed aspects that hindered the effectiveness of resocialization policies within socio-educational units, including overcrowding, limited family visits, and the continued focus on punitive measures in socio-educational actions. The study also identified a lack of partnerships with professional institutions, courses that do not meet the technical level of adolescents, and the absence of public resources to support employment initiatives. Therefore, the conclusion is that the socio-educational system faces challenges in implementing the fundamental rights and guarantees of young individuals in conflict with the law, with ongoing restrictions that compromise juvenile justice and resocialization.
Keywords: Resocialization; Socio-Educational Measures; Juvenile Offenders